Laughing at myself : my education in Congress, on the farm, and at the movies - Glickman, Dan (University Press of Kansas, 2021)
"In Laughing at Myself, Dan Glickman-a Jewish kid from Wichita, Kansas, descended from Russian and Eastern European immigrants-tells the story of his life in public service as a principled moderate driven by the values of pragmatism and civility. After leaving the Republican Party in 1974, he represented the 4th Congressional District of Kansas as a Democrat in the US House of Representatives for eighteen years. He went on to become the US Secretary of Agriculture in the Clinton administration and later served as Chairman of the Motion Picture Association of America, Inc. In the midst of a highly polarized and partisan political climate, Glickman's life highlights the value of building bridges between rivals, rather than making enemies. Told with self-deprecating humor and a belief in the "better angels of our nature," Laughing at Myself encourages people to see that common sense and moderation are the keys to a meaningful life in service to the common good. Laughing at Myself is a regional trade manuscript that reflects the University Press of Kansas's aim to serve the Kansas and wider Midwestern and Great Plains regions. As a memoir by a former Congressman and presidential cabinet member, the book also advances the Press's interest in the fields of American politics and US history. Dan Glickman's story will resonate especially for Kansans while also offering perspectives on important political moments that will be of interest to a wider audience of informed readers"--